Post-marketing safety surveillance of voclosporin: an observational, pharmacovigilance study leveraging faers database study on the safety of voclosporin - Wang, Zhi; Lang, Yanhua; Liu, Xuyan; Wang, Yuxuan; Shao, Leping (Frontiers in Pharmacology, 2025)
BackgroundVoclosporin is a novel calcineurin inhibitor approved for the treatment of adult active lupus. Based on the US Food and Drug Administration Adverse Event Reporting System FDA Adverse Event Reporting System database, this study conducted a comprehensive evaluation of the safety characteristics of voclosporin in clinical use.MethodsWe selected data from the FAERS database from the 2021Q1 to 2024Q2. Disproportionality analysis was employed to detect positive signals at the System Organ Class (SOC) and Preferred Term (PT) levels. Our analysis encompassed the time to onset, and subgroup analyses stratified by gender and age.ResultsThere are 3,407,094 reports collected from the FAERS database, of which 4,013 reports listed voclosporin as the “primary suspected” drug. Eight positive SOC signals and 138 positive PT signals were identified, including some unexpected signals that were not listed on the drug label such as menstrual disorder (n = 7, ROR = 5.82) and acute pulmonary oedema (n = 3, ROR = 4.16). Gender differences and age differences existed in PT signals related to voclosporin. Nearly one-third of the adverse events occurred within the first month after voclosporin initiation, with a median onset time of 99 days.ConclusionThis study clarified the characteristics of voclosporin-related adverse drug reactions, providing strong support for clinical monitoring and risk identification of voclosporin.